Respiratory Protection: Lessons Learned from a Global Pandemic - Figueroa M; McMullen KM; Kruger E; Peterson AV; Johnson C; Line W (Dove Medical Press, 2023)
Marta Figueroa,1 Kathleen M McMullen,2 Elizabeth Kruger,3 Amanda Vancene Peterson,4 Caroline Johnson,5 Whitney Line6 1Environmental Health and Safety, NYU Langone Health, New York, NY, USA; 2Infection Prevention, Christian Hospital and Northwest Healthcare, St. Louis, MO, USA; 3Home Infusion and Infection Prevention, Park Nicollet Health Services, St. Louis Park, MN, USA; 4Intensive Care Unit, United Hospital, St. Paul, MN, USA; 5Personal Safety Division, 3M Company, St. Paul, MN, USA; 6Medical Solutions Division, 3M Company, St. Paul, MN, USACorrespondence: Marta Figueroa, Email Marta.Figueroa@nyulangone.orgAbstract: The COVID-19 pandemic exposed the limitations of global health systems' abilities to manage the rapid spread of a novel infectious disease, which was exacerbated by shortages of respiratory protective devices and other critical personal protective equipment (PPE). An advisory panel of experienced health-care professionals with backgrounds in Occupational and Environmental Health and Safety (OEHS), Infection Prevention, Nursing, and Clinical Application Specialists convened to discuss challenges and strategies associated with the selection and use of respiratory protective devices as experienced during the first year of the COVID-19 pandemic. This discussion led to the following recommendations: 1) the need for clear communication of alternative respiratory protection selection and use recommendations in accordance with US regulatory and agency guidance; 2) the need for collaboration between Infection Prevention, OEHS, clinical staff, supply chain/materials management, emergency preparedness, executive leadership, and finance; 3) the need for adequate stockpiling, inventory rotation, and diverse respiratory protection options to accommodate the majority of health-care workers; 4) the need for efficient and innovative strategies to communicate evolving regulatory, agency, and facility recommendations and to deliver appropriate training on respiratory protection; and 5) the need for additional research on respiratory protection use - involving filtering facepiece respirators (FFRs) as well as other respirator types designed to be reused - to balance infection prevention best practices with a sustainable process. In conclusion, these considerations may offer guidance and identify areas for research on preparedness, communication, education, and training to enhance the preparation of health-care facilities including community-based health-care organizations for unexpected public health events.Keywords: COVID-19, personal protective equipment, PPE, filtering facepiece respirator, infection prevention, environmental health and safety, nursing